Expanding the phenotypic spectrum of KCNK4: From syndromic neurodevelopmental disorder to rolandic epilepsy - Yan, Hong-Jun; He, Yun-yan; Jin, Liang; Guo, Qiang; Zhou, Jing-Hua; Luo, Sheng (Frontiers in Molecular Neuroscience, 2023)
The KCNK4 gene, predominantly distributed in neurons, plays an essential role in controlling the resting membrane potential and regulating cellular excitability. Previously, only two variants were identified to be associated with human disease, facial dysmorphism, hypertrichosis, epilepsy, intellectual/developmental delay, and gingival overgrowth (FHEIG) syndrome. In this study, we performed trio-based whole exon sequencing (WES) in a cohort of patients with epilepsy. Two de novo likely pathogenic variants were identified in two unrelated cases with heterogeneous phenotypes, including one with Rolandic epilepsy and one with the FHEIG syndrome. The two variants were predicted to be damaged by the majority of in silico algorithms. These variants showed no allele frequencies in controls and presented statistically higher frequencies in the case cohort than that in controls. The FHEIG syndrome-related variants were all located in the region with vital functions in stabilizing the conductive conformation, while the Rolandic epilepsy-related variant was distributed in the area with less impact on the conductive conformation. This study expanded the genetic and phenotypic spectrum of KCNK4. Phenotypic variations of KCNK4 are potentially associated with the molecular sub-regional effects. Carbamazepine/oxcarbazepine and valproate may be effective antiepileptic drugs for patients with KCNK4 variants.